Validation and Development of the Guidebook of Barambai Kolam Kanan Dragonflies Species to Increase Science Process Skills - Uthami, Mariza; Winarti, Atiek; Biyatmoko, Danang; Noor, Ihsan (Technium Education and Humanities, 2024)
The biodiversity and diverse habitat of dragonflies in Kalimantan have an enormous potential that can be identified in various fields, one of which is the field of education. Utilizing local potential as teaching materials, one of which is the Guidebook, is considered capable of supporting learning. Skills are trained in learning activities, including science process skills. This study aims to describe the Identification Handbook's validity, practicality, and effectiveness. The stages of development conducted are self-evaluation, expert test by three lecturers of Master of Biology Education at Hull Mangkurat University, individual trial of three students, small group test of five students, and significant group test of twenty undergraduate Biology Education students who have passed the Invertebrate Zoology course. The research results of the Dragonfly Identification Guidebook are the validity of the Dragonfly Identification Guidebook score of 3.44 with a very decent category and the effectiveness of the overall N-Gain average of 0.6 with a medium category that can be implemented in learning.